INTERAKSI NEUROSAINS HOLISTIK DALAM PERSPEKTIF PENDIDIKAN DAN MASYARAKAT ISLAM - Rusdianto, Rusdianto (State Institute of Islamic Studies (IAIN) Palu, 2015)
This article discusses the interaction neorosains holistic education in the perspective of Islam. The concept of Islamic education is the interaction of neuroscience holistic in building the social structure that is controlled through the instru-mentation of morality, values, mind control, brain function mind and looked at society as a whole. Holistic neuroscience principles include the principle of commanding the good and forbidding the evil, the principle of integration of science, the principle of solidarity towards the poor, the principle of the spirit of devotion, tajdid principle, the principle of democracy and society. It thus becomes very possible for Muslims to make a picture of an ideal society based pejunjuk Koran.